On the impact of on-chip inductance on signal nets under the influence of power grid noise. - Chen, T. (IEEE Transactions on VLSI systems)
It has been well recognized that the impact of on-chip inductance on some critical nets, such as clock nets, is significant and cannot be ignored in delay modeling for these nets. However, the impact of on-chip inductance on signal nets in general is still not well understood. We present results of analyzing inductive effects on signal nets for ultradeep submicron technologies under the influence of power grid noise. The analysis is based on an Al-based 0.18-μm CMOS process and a Cu-based 0.13-μm CMOS process. The impact of on-chip inductance is shown to be insignificant if we assume a perfect power supply network around the interconnect routes. Otherwise, the impact of on-chip inductance can be significant. Furthermore, the results presented in this paper illustrate the impact of on-chip inductance one would expect from transitioning from an Al-based interconnect technology to a Cu-based interconnect technology. A heuristic method is proposed in the paper to account for the inductive coupling due to power grid noise in signal delay modeling and simulations.